The Conceptions of Modesty and Modest Dress in the Scriptures of Abrahamic Religions: Konsep Kesopanan dan Pemakaian Sederhana Wanita dalam Teks Agama-Agama Ibrahim - Sadatmoosavi, Zohreh; Wan Ali, Wan Zailan Kamaruddin; Shokouhi, Mohammad Ali (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
Over the past two decades, the issue of modesty norms and women’s wearing modest dress were widely discussed in academic and media discourse. Basically, modesty does not belong to any specific culture but today it has become the subject of intense scrutiny in the Islamic context. However, all scriptures of Abrahamic religions; the Qur’an, Old and New Testaments have emphasized on the observing modesty as a moral and social virtue for both men and women and recommended modest dress for women despite of using different conceptions and terms. In addition, historically and traditionally, among the followers of these religions observing modest behaviors has been regarded as religious commandment. This research will explore the conceptions of modesty and modest dress of women in Judaism, Christianity and Islam to clear the essential similarities of Abrahamic faiths regarding to modesty norms and using modest dress for women and their significance.